Deracemisation of alpha-amino acids - (R)- and (S)-phenylalanine from the same enantiomer of a homochiral auxiliary - Bull, S; Davies, S; Epstein, S; Ouzman, J (1998)
Chiral auxiliary (3S)-N,N'-bis-(p-methoxybenzyl)-3-isopropylpiperazine- 2,5-dione 1 was employed for the synthesis of both enantiomers of phenylalanine using a regioselective deprotonation/stereoselective reprotonation strategy. Modification of this approach enables the efficient deracemisation of (±)-phenylalanine.